(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
Antidiabetic action of ethanolic extracts of seed and rind of Punica granatum L. was evaluated on alloxan-induced diabetic albino rats. Both the extracts, each at a dose of 200mg/kg/d, were administered orally for two weeks to alloxan-induced diabetic rats. Blood glucose was estimated every week for two consecutive weeks. For evaluation of probable mechanism of action of the extracts, glycogen estimation was carried out in liver, heart and skeletal muscle and effect on adrenaline-induced hyperglycemia was observed. Both the extracts significantly (p<0.05) reduced the rise in blood glucose induced by alloxan, with the rind extract exhibiting significantly (p<0.05) better activity than seed extract. Both the extracts also produced significant (p<0.05) increase in liver glycogen and significantly (p<0.05) reduced adrenaline-induced hyperglycemia. These results support strong antidiabetic action in favor of P. granatum seed and rind extracts Key words: Punica granatum L.; Ethanolic extracts; Antidiabetic; Alloxan. DOI: 10.3329/sjps.v2i1.5810 Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 14-21